Real time experimental performance investigation of a NePCM based photovoltaic thermal system: An energetic and exergetic approach. (July 2021) - Islam, M.M.; Hasanuzzaman, M.; Rahim, N.A.; Pandey, A.K.; Rawa, M.; Kumar, L.
Abstract: Photovoltaic thermal (PVT) systems have emerged as a well-engineered upgradation of photovoltaic (PV) modules that deliver both electricity and heat simultaneously. However, practicable performance is yet to be realized from these systems on commercial basis. In the present research, nanoparticle enhanced phase change material (NePCM) has been incorporated to improve the thermal and electrical performance of a PVT system. Outdoor experimental investigation of five different systems, namely, PV, PVT, PV-PCM, PVT-PCM and PVT-NePCM has been carried out concurrently under real time Malaysian climatic conditions. Experiments have been conducted at flow rates from 0.5 to 4.0 L/min. Real time temperatures of the ambient, heat transfer fluid (HTF) and PV cell, humidity of air, wind velocity and fluid flow rate have been recorded through a digital data acquisition system. Performance of the systems have been analyzed applying both energy and exergy methods. Results show that PVT-NePCM system raised water outlet temperature by more than 46 °C. This system attained a maximum overall energy efficiency of 85% and a peak exergy efficiency of 12%. Integration of nano composite PCM in thermal regulation of PVT systems will pave the way for efficacious commercialization of these systems because of the possibility of their nighttime applications. Highlights: Experimental investigation of nano enhanced phase change material (NePCM) based PVT. Latent heat capacity of PCM is fairly enhanced by the insertion of MWCNT. PVT-NePCM system reduce cell temperature 4 °C more than PVT-PCM system. PVT-NePCM system raises water outlet temperature by more than 46 °C. Maximum overall energy and exergy efficiency are 85.3% and 12%, respectively.